Analisis Perkembangan Moral Anak Sekolah Dasar Berdasarkan Teori Piaget dan Kohlberg - Furroyda, Amanda Fathin; Widhyahrini, Khusna (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the stages of moral development in students based on Piaget and Kohlberg's theories, the factors that cause moral decline in children, especially elementary school children, and alternative solutions. In addition, this study also discusses what kind of educational services can be implemented to prepare good moral education for children, considering that school is also a crucial place in shaping children's morals. The method used is a literature study by reviewing various relevant literature sources related to moral development in children. The results of the study show that the moral stages in children are divided into three levels consisting of six stages. The first level is preconventional, the second level is conventional, and the third level is postconventional. This study identifies factors that cause a decline in children's morals, such as a lack of religious education, an unstable social environment, a poor home environment, and exposure to illegal drugs. In addition to the family and social environment, schools play a very important role in shaping children's morals. Therefore, there is a need for strategies in school services to create moral students.